Istoadenoma do ducto biliar comum - Andrade Filho,José de Souza (2000)
Biliary duct cystoadenomas are rare neoplasms, with about 120 cases described in the literature, including cystoadenomas and cystoadenocarcinomas. The authors report a case of cystoadenoma of the common bile duct in a 45-year-old woman with history of jaundice. Ultrasound revealed a cystic mass located in the common bile duct. Endoscopic retrograde cholangiopancreatography showed a negative filling defect in the proximal third of the common bile duct, a finding unique to our case. Total excision of the mass, cholecystectomy and an end-total anastomosis with a T-tube choledochostomy, were performed. Histological examination revealed a multicystic lesion with cavities lined by mucinous columnar non-ciliated epithelium, with surrounding densely cellular stroma resembling ovarian stroma. Six years after surgery the patient is alive and well, with no complains referring to the hepatobiliary tract. No abnormalities are presently detected in the biliary tree, ultrasonographically.